Pengaruh media sosial terhadap keputusan pembelian yang dimediasi oleh citra merek - Iskandar, Ferdinand Hansen; Assa, Adrie Frans (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Technological developments that occur at this time are growing rapidly, one of which wecan feel is the media of communication. This development is also supported by theemergence of online-based applications such as social media that help provide usefulinformation for its users. This of course also affects the world of marketing directly. Thisstudy aims to determine the effect of social media on purchasing decisions mediated bybrand image (a case study of undergraduate students at Krida Wacana ChristianUniversity in 2018, 2019, 2020 & 2021). The population in this study were active studentsof UKRIDA Class of 2018, 2019, 2020, and 2020 with a total of 2546 students. The numberof samples taken as many as 94 people using simple random sampling technique. Theresults of this analysis explain that all indicators in this study are valid and reliable. Thisstudy uses a Structural Equation Modeling (SEM) approach based on Partial Least Square(PLS) using SmartPLS 3.3 software. This study found that social media had a significanteffect of 31.5% on brand image, as well as social media on purchasing decisions only45.8% which can be explained in this study, meaning that there are about 68.5% of brandimage variables and 54. ,2% of the purchasing decision variables that can be explainedfrom other variables outside the study